Bangladesh Economic Update, September 2011 - World Bank (Washington, DC, 2017)
Real gross domestic product (GDP) grew at 6.7 percent in FY11, continuing the upward trend in growth after declining during FY06-09. This strong performance can be repeated in FY12 if exports continue to grow and if garment exports benefit from the agreement reached during the recent India-Bangladesh Summit, remittances continue to recover, and if investment is boosted by improved infrastructure services particularly power. Risks in the global economy can affect Bangladesh in several ways. The standard and poor (S&P) downgrade of US debt as well as the debt problems in the Euro Zone are affecting the international markets and renewing fears of another global slowdown. This time around, limited fiscal and monetary space in developed countries increases the chances of a protracted slowdown. If this slowdown occurs, it can affect Bangladesh's balance of payments through its impact on exports and remittances, put pressure on the exchange rate, increase economic uncertainty, and, in turn, weaken investment and growth. Domestic policies will also affect Bangladesh's economic prospects. A slow pace of reforms in the investment climate can affect domestic and foreign investment, as can inadequacies in energy supply and the poor quality of roads. The reversal of trade reforms as well as weakening of the financial sector can also affect export growth and investment. Expansionary macroeconomic policies could increase risks on the current account and make inflation management more difficult. Unlike in 2008, Bangladesh has insufficient policy space to cushion the impact of a second global slowdown through fiscal stimulus. packages and monetary easing. Rapid growth in subsidies, sustained high rate of growth of credit to the private sector as well as recourse to monetary financing of the fiscal deficit have led to the erosion of the fiscal and monetary policy space. Much improved fiscal and monetary discipline combined with stronger efforts to address the energy and infrastructure deficits will be critical for sustaining growth performance. Maintaining the long-established tradition of sound macroeconomic management will also be important.